HARMONY AS A CONCEPT OF CREATION BONE BASED ACCESSORIES AT PT. KIRANA'S IMAGINATION HOUSE, JIMBARAN, BADUNG, BALI - Widhi Adnyana, I Wayan; I Made, Suparta; I Nyoman, suardina (Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
The creation of accessories made of bone with the concept of harmony is one of the answers to the phenomenon that occurs in the fashion world, where the fashion world sometimes overrides accessories in its manifestation. In fact, accessories and the fashion world have a relationship and dependence on each other, so accessories have an important role in the fashion world to add to the perfection of the appearance of fashion works. This phenomenon is interesting to reveal by creating a set of fashion accessories products with the concept of harmony taking the shape of roses as an exploration space that is in harmony with the shape of roses that have harmony, unity of shape, color and fragrance forming an amazing harmony frame. Through the creation of this fashion accessories product, it is hoped that it will provide a further understanding for fashion designers as well as the general public that accessory products can raise the dignity and value of fashion itself. The creation process uses the method proposed by Sp Gustami (2007:329) through three stages and six steps, namely exploration, design, and embodiment. Exploration includes exploration activities to explore creative sources. The design is built based on the acquisition of items from the results of the analysis formulated in the visualization of the idea of sketch form as a design reference. The embodiment of making a model according to the selected sketch becomes a prototype model until the perfection of the desired product shape is found. The result Based on exploration, experimentation of techniques, materials, innovations and using carving techniques with a tuner drill produced five sets of accessories with the titles Urn of Life, Compassion, Life Cycle, Charisma, and Three Brothers, which have applicative power in the world of fashion design.